Assessment of laryngeal cancer in patients younger than 40 years. (27th October 2017) - Nachalon, Yuval; Alkan, Uri; Shvero, Jacob; Yaniv, Dan; Shkedy, Yotam; Limon, Dror; Popovtzer, Aron
Abstract : Objectives/Hypothesis: To assess the differences between patients with laryngeal squamous cell carcinoma under 40 years old and those 40 years old or older. A secondary objective was to compare survival outcome between these cohorts. Study Design: Retrospective chart review. Methods: We reviewed the medical charts of all patients treated in our tertiary referral center for laryngeal squamous cell carcinoma from 2005 to 2014. Patients aged < 40 years at diagnosis were compared to older patients. Results: The study group comprised 160 patients. Of them, 13 were aged < 40 years at diagnosis. Mean age was 35 ± 3.9 years and 64.4 ± 11 years for the two groups. Among the younger patients, 38% were smokers (mean pack/day, 2.2) versus 71% in the older group (mean pack/day, 3). The younger group typically had a more advanced stage than the older group at presentation; eight young patients (62%) had stage III or IV versus 49 (33%) in the older group ( P  = .042). Mean overall survival was 6.7 ± 1 years for those under 40 years old and 7.7 ± 0.2 years for the older patients ( P  = .2). The 5‐year survival rate was 69% for young patients and 90% for the older group ( P  = .04). However, there was no significant between‐group difference in overall survival or 5‐year survival rate when stratified for early‐ and late‐stage disease. Conclusions: There is a lower prevalence of classic risk factors in younger patient with laryngeal carcinoma in this study, suggesting a different etiology compared to our older cohort. The under‐40 cohort presented with more advanced disease and had a worse 5‐year survival; however, when stratified for early‐ versus late‐stage disease, there was no significant difference in overall or 5‐year survival between the groups. This may suggest that, despite a different etiology, laryngeal cancer behaves similarly in older and younger patients. Level of Evidence: 4. Laryngoscope, 128:1602–1605, 2018